A58 REGULATION OF INTESTINAL EPITHELIAL THYMIC STROMAL LYMPHOPOIETIN GENE EXPRESSION BY RETINOIC ACID RECEPTOR ALPHA. (26th February 2020) - Mahmood, R; Chan, R; Beck, P; Jijon, H
Abstract: Background: We have targeted the retinoic acid receptor alpha (RARα) isoform in murine intestinal epithelial cells (IECs) to explore the role of epithelial intrinsic retinoid signaling in intestinal immune homeostasis. We noted a significant decrease in the CD11c+ and CD103+ dendritic cell (DC) subpopulations in the intestines of intestinal-epithelial specific RARα-deficient (RARα villin ) mice. In the present study, we identified Thymic Stromal Lymphopoietin (TSLP) as a contributing factor that influences intrinsic RARα signaling within IECs. This cytokine preferentially stimulates CD103+ DCs to a more tolerogenic phenotype in the GI tract, induces Tregs and drives TH 2 polarization. TSLP also influences immune homeostasis by modulating the activation of myeloid cells, inhibition of proinflamamtory DCs, and production of IL-12. Notably, TSLP levels are decreased in Crohn's disease (CD) where inflammation is driven by IL-12. Aims: We hypothesize that RA intrinsic signaling within IECs modulates TSLP expression via activation of RARα. We sought to generate a RARα -/- murine intestinal epithelial cell line utilizing the CRISPR/CAS9 system to examine the effects of RARa ablation. Second, we aim to establish RARα's role in regulating intestinal epithelial TSLP expression in both the RARα villin mice and the CRISPR-generated RARα -/- cell line. Methods: Exon 5 in the open reading frame of the RARα gene in Mode-K murine IECs was targeted using CRISPR/CAS9. CRISPR cleavage and knockdown of RARα activity was confirmed via surveyor/luciferase assays. The cell lines were phenotyped with regards to their morphology, proliferative ability, and viability. Next, we examined TSLP mRNA expression in the colons of RARα villin mice and the CRISPR RARα -/- knockout cell line via qRT-PCR under baseline and stimulated conditions. Wild-type (WT) and RARα-/- cells were stimulated with RARα-selective agonist, BMS753, and muramyl dipeptide (MDP), a NOD2-selective agonist. Results: TSLP expression in surface colonic epithelium was elevated 2.3-fold in RARα villin mice compared to WT litter mates. TSLP expression was elevated 10-fold in the Mode-K RARα-/- cells versus parent cells at baseline. BMS753 stimulation resulted in a 15-fold increase in TSLP expression in the RARα-/- cells compared to baseline. When stimulated with MDP, a NOD2-selective agonist known to stimulate TSLP expression, TSLP expression was elevated 60-fold in the RARα-/- cells, but significantly impaired compared to the WT cells (400-fold). Conclusions: TSLP expression is controlled by RARα in colonic IECs where it may act as a repressor of TSLP promoter transactivation under baseline conditions. This suggests an important role for RA on myeloid and T cell function via effects on intestinal epithelial TSLP expression. Funding Agencies: CCCUniversity of Calgary, Department of Medicine